Pengembangan Bahan Ajar PJOK Berbasis Life Skills Pada Materi Renang Untuk Siswa Sekolah Dasar: Indonesia - Matitaputty, Johanna; Ratumanan, Tanwey Gerson (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop teaching materials for Physical Education, Sports and Health (PJOK) based on life skills in swimming material for elementary school students. The development was carried out to answer the challenges in learning PJOK, especially in the aspect of integrating life skills values. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). The research subjects were fifth grade students of SD Negeri Inpres 42 Ambon. Data collection techniques included expert validation questionnaires, observations, and student response questionnaires. The results showed that the teaching materials developed were classified as very feasible based on the validation results and obtained positive responses from students. This teaching material is able to develop life skills such as cooperation, responsibility, courage, and personal safety in the context of swimming learning.